International exchange: reflections on the Fifth Nanzan Seminar for the Study of Japanese Religions# - Graf, Tim (Bulletin of the Nanzan Institute for Religion & Culture, 2020)
Based on the observation that some Buddhist temples were able to profit from the covid-19 epidemic while others suffered catastrophic losses in income, this article examines Buddhist responses to the novel coronavirus across an economic divide. In introducing case studies, I outline a broad spectrum of practices, soteriologies, and temple management styles. The first part on divine protection focuses on Banshōji, a popular prayer temple in downtown Nagoya. Banshōji experienced record sales in prayer rituals during the pandemic. I then situate these findings within the broader context of discourse on religion after the March 2011 disasters, which leads me into questions regarding post-pandemic religious innovation and Buddhism’s role as a social contributor in times of epidemics and crises. The final part suggests that the priests most vulnerable to covid-19 related disruptions, namely social distancing measures, are those who used to make a living by participating in larger funerals at various temples and sites with-out managing a temple or parish community of their own.